Effects of pilates method on flexibility in lower limb of college soccer players (Revista de Investigaciones Universidad del Quindío, 2013)
Objective: To determine the effects of Pilates on the flexibility of the lower limbs in college football, compared to a traditional method. Materials and Methods: A quasi-type quantitative approach with experimental and control group pre and post with the participation of 80 players, equally distributed in each group. Results and conclusions: univariate and bivariate analysis allowed statistically significant evidence of joint mobility in flexion, extension, abduction, adduction, internal rotation, external rotation of the hip joint, knee flexion, dorsiflexion and plantarflexion of ankle between pre-test and post-test experimental group. As for special tests of muscle elasticity is statistically significant changes in the iliopsoas, hamstrings, rectus femoris pre-test and post-test experimental group. Based on the foregoing the Pilates method should become a standard training method for athletes and the community at large.
Keywords: education and physical training; flexibility; Exercising; football; (Descriptors DeCs)